Effects of Operating Pressure, Nozzle Diameter and Wind Speed on the Performance of Sprinkler in Irrigation System during Water Application - Nigatie, Dereje Bishaw; Dinka, Megersa O.; Hordofa, Tilahun (ABC Journal of Advanced Research, 2018)
Owing to an increasing demand for irrigation water associated with the massive expansion of irrigated sugarcane farms in Ethiopia, there is a need to use the available water efficiently and effectively. Accordingly, a study was conducted to evaluate the effect of operating pressure and nozzle size on the field performance of dragline sprinkler system at Wonji/Shoa Sugar Estate. The study was conducted under three wind phases (morning, mid-day and late afternoon) using three operating pressures (250 kPa, 300 kPa and 350 kPa) and two nozzle sizes (4.4 and 4.8 mm). Uniformity measurements were performed using single sprinkler and four sprinklers configurations. An application efficiency of low-quarter of 41% to 80.3% and actual application efficiency of low-quarter of 30.1% to 37.5% were achieved under the respective test combinations. Christiansen’s coefficient of uniformity of 71.7% to 86.3%, and distribution uniformity of 61% to 80.3% were achieved under different test combinations for four sprinklers test. The achievable delivery performance ratio was in the range of 0.81 to 1.18. The experimental results illustrated that, lower operating pressure and higher wind velocity were the major factors responsible for the low water distribution uniformity and efficiency.